1989
DOI: 10.1111/j.1600-0528.1989.tb00645.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental status in a group of adult diabetic patients

Abstract: The aim of this study was to determine the prevalence of dental caries, DMFT score and treatment needs in a group of diabetic patients (n = 222), mean age 46.9 yr, and to compare them to those recorded in a control group (n = 189), mean age 43.9 yr, using WHO criteria. Relations between the type and duration of diabetes mellitus, diabetic complications (retinopathy and neuropathy), diabetic control, and the subjects' DMFT status were separately studied. The results obtained revealed no difference in the preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
2
5

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 12 publications
2
27
2
5
Order By: Relevance
“…Poor metabolic control appears to associate with dental caries (Pohjamo et al 1988, Twetman et al 1992), but this is not found by Bacic et al (1989). As far as the duration of diabetes is concerned, the incidence of dental caries in children is higher during the first year of diabetes than during the second year (Twetman et al 1992), while no association between the duration of diabetes and dental caries is found by Bacic et al (1989).…”
Section: Dental Cariesmentioning
confidence: 82%
See 2 more Smart Citations
“…Poor metabolic control appears to associate with dental caries (Pohjamo et al 1988, Twetman et al 1992), but this is not found by Bacic et al (1989). As far as the duration of diabetes is concerned, the incidence of dental caries in children is higher during the first year of diabetes than during the second year (Twetman et al 1992), while no association between the duration of diabetes and dental caries is found by Bacic et al (1989).…”
Section: Dental Cariesmentioning
confidence: 82%
“…Contrariwise, diabetic patients have been shown to have lower dental caries levels (Albrecht et al 1988, Kirk & Kinirons 1991. Further, no differences have been found in the caries level (Tenovuo et al 1986, Bacic et al 1989, Falk et al 1989, Pohjamo et al 1991 or the root caries level (Tavares et al 1991) between diabetic and non-diabetic patients.…”
Section: Dental Cariesmentioning
confidence: 99%
See 1 more Smart Citation
“…La controversia acerca de si los sujetos afectados por DM son más pronos a la caries reside en el hecho que así como en la presente investigación se encontró una asociación entre caries radicular y DM, otros reportes no la han detectado (3,11,12) . La caries radicular se produce en la gran mayoría de los casos una vez que las raíces son expuestas al medio oral (25) , por ello, no es de extrañar que exista una mayor prevalencia de caries radiculares entre los diabéticos, toda vez que esta población presenta mayores tasas de enfermedad periodontal que sujetos libres de la patología (4) .…”
Section: Discussionunclassified
“…En particular, la DM podría jugar un rol, toda vez que genera cambios en el ecosistema oral, los que podrían afectar la susceptibilidad a la caries dental. Pese a lo anterior, la asociación entre DM y un mayor riesgo de caries no ha sido bien establecida, ya que mientras algunos autores señalan una leve mayor tasa de caries entre pacientes diabéticos (10) , otros estudios no han encontrado una asociación significativa (3,11,12) . Se ha reportado que los pacientes diabéticos tendrían mayor prevalencia de caries radiculares, pero no coronarias (13) .…”
unclassified